'I do not know where it comes from, I am suspicious of some childhood trauma' association of trauma with psychosis according to the experience of those affected. Issue 1 (1st January 2021) - Hurtado, María M.; Villena-Jimena, Amelia; Quemada, Casta; Morales-Asencio, José Miguel
ABSTRACT: Background: Trauma-related symptoms are often experienced after a first psychotic episode. Objective: In this study, we conduct a qualitative analysis of referred traumatic experiences of outpatients diagnosed with psychotic disorders. Method: Focus groups were formed and in-depth interviews conducted with 30 participants, focusing on their experience with the disorder and the health care received. Given the frequency with which trauma and psychosis have been associated in the scientific literature, the nature of this relation is addressed as a secondary objective, via a qualitative analysis. Results: Analysis revealed two main themes in the patients' discourse. On many occasions, traumatic experiences were related to the development of the disorder. Although most participants referred to traumatic experiences during childhood, episodes during adult life were also reported, which may have triggered the disorder. The second theme was that of the interlocking relationship between the psychotic experience and certain coercive practices undergone during the provision of health care for psychosis, and the traumatic effects thus generated. Conclusions: The participants considered both themes to be highly important. Accordingly, these issues should be carefully assessed and managed in order to provide appropriate person-centred care. HIGHLIGHTS: A qualitative analysis was conducted of the association between trauma and psychosis. Participants identified early-life trauma, such as child abuse, as the origin of their disorder. Further trauma was generated by experiences after the onset of psychosis, including practices in health care settings.